Effects of thymol supplementation on performance, mortality and branchial energetic metabolism in grass carp experimentally infected by Aeromonas hydrophila - Morselli M.B.* (2020)
© 2019 Elsevier LtdWe determined whether thymol supplementation of would minimize the negative effects of Aeromonas hydrophila infection on branchial energy metabolism, weight loss and mortality in grass carp (Ctenopharyngodon idella). We found that the infected fish all died, while 62.5% of those supplemented with 100 mg/kg thymol survived. Cytosolic and mitochondrial creatine kinase (CK) activities, as well as adenylate kinase (AK) and pyruvate kinase (PK) activities were significant lower in gills of A. hydrophila-infected fish than those of the control group, and adenosine triphosphate (ATP) levels were significant lower in the infected group. Finally, branchial reactive oxygen species (ROS) were significant higher in A. hydrophila-infected fish than in the control group. Supplementation with 100 and 300 mg thymol/kg diet prevented inhibition of branchial cytosolic and mitochondrial CK activities caused by infection, and also inhibited the reduction of branchial ATP levels. Supplementation with 100, 200 and 300 mg thymol/kg prevented the inhibition of branchial AK and PK activities induced by aeromonosis. Supplementation of 100 mg thymol/kg prevented weight loss after A. hydrophila infection. These data suggest that supplementation with 100 mg thymol/kg exerts potent bactericidal properties and augments longevity. Supplementation at all concentrations of thymol prevented A. hydrophila-induced branchial bioenergetics; nevertheless, higher concentrations were associated with side-effects.